Der Russische Interdiskurs und seine Entwicklung Eine kultur- und diskurstheoretische Analyse am Material von Schulbuechern (1986-1991 und 1993-1997) - Notarp, Ulrike (Slavistische Beitraege, 2001)
The present work is an empirical analysis of Soviet Socialist and Russian textbooks. Its aim is to reconstruct essential parts of the Soviet and Russian interdisciplinary discourse. It should be found out how the Soviet and Russian interdisciplinary content is structured and how it is socialized in textbooks. The underlying problem of the work as a whole is the question of the possibilities of describing and explaining the culture-specific language or culturally marked communication which generally occurs in cultures and the mechanisms of their functioning. It is therefore about the explanation of the phenomenon of "culture-specific communication", which is known from everyday experience, which becomes particularly obvious, for example, if one does not feel understood in a foreign culture or can not understand the behavior of others, precisely because it is " culturally specific "is different from what is taken for granted and" normal "in one's own culture.